Shifting the Paradigm of Testosterone Replacement Therapy in Prostate Cancer - Bell, Michael A. (World J Mens Health, 2018)
Historically, testosterone and prostate cancer have been demonstrated to have a positive association leading providers to forgo testosterone replacement therapy (TRT) in men with concurrent histories of hypogonadism and prostate cancer. This paradigm has been gradually shifting with our evolving understanding of the relationship between testosterone and prostate cancer and the gaining popularity of the saturation model. Newer data suggests improved quality of life for men with hypogonadism after TRT leading to a more tempered view of the effects of this treatment and its risk in prostate cancer. As more reports emerge of TRT in men who have either undergone definitive treatment for prostate cancer or are on active surveillance, some providers see a role for TRT in these patients despite non-consensus in clinical guidelines. It is critical that we examine evidence currently available, while we await more rigorous data to emerge.